Antarctic Sphingomonas sp. So64.6b showed evolutive divergence within its genus, including new biosynthetic gene clusters - Núñez-Montero, Kattia; Rojas-Villalta, Dorian; Barrientos, Leticia (Frontiers in Microbiology, 2022)
The antibiotic crisis is a major human health problem. Bioprospecting screenings suggest that proteobacteria and other extremophile microorganisms have biosynthetic potential for the production novel antimicrobial compounds. An Antarctic Sphingomonas strain (So64.6b) previously showed interesting antibiotic activity and elicitation response, then a relationship between environmental adaptations and its biosynthetic potential was hypothesized. We aimed to determine the genomic characteristics in So64.6b strain related to evolutive traits for the adaptation to the Antarctic environment that could lead to its diversity of potentially novel antibiotic metabolites. To do this, the complete genome sequence of the Antarctic strain was obtained and mined for Biosynthetic Gene Clusters (BGCs) and other unique genes related to adaptation to extreme environments. Comparative genome analysis based on multi-locus phylogenomics, BGC phylogeny, and pangenomics were conducted within the closest genus, aiming to determine the taxonomic affiliation and differential characteristics of the Antarctic strain. Our So64.6b strain showed a closest identity with Sphingomonas alpina, however containing a significant genomic difference of ortholog cluster related to degradation multiple pollutants. Strain So64.6b had a total of six BGC, which were predicted with low to no similarity with other reported clusters; three were associated with potential novel antibiotic compounds using ARTS tool. Phylogenetic and synteny analysis of a common BGC showed great diversity between Sphingomonas genus but grouping in clades according to similar isolation environments, suggesting an evolution of BGCs that could be linked to the specific ecosystems. Comparative genomic analysis also showed that Sphingomonas species isolated from extreme environments had the greatest number of predicted BGCs and a higher percentage of genetic content devoted to BGCs than the isolates from mesophilic environments. In addition, some extreme-exclusive clusters were found related to oxidative and thermal stress adaptations, while pangenome analysis showed unique resistance genes on the Antarctic strain included in genetic islands. Altogether, our results showed the unique genetic content on Antarctic strain Sphingomonas sp. So64.6, –a probable new species of this genetically divergent genus–, which could have potentially novel antibiotic compounds acquired to cope with Antarctic poly-extreme conditions.